PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Amelia Amelia; Tri Diana (Jurnal Ekonomi Integra, 2023)
The purpose of this reasearch is to give empirical evidence about the relationship between working capital management to profitability  for companies and investors. This research uses purposive sampling method as sampling method. The population of this research is manufacture companies that are listed on Indonesian Stock Market from 2018 to 2020 with 30 sample in total. This research have independent variables which are working capital factors with variable measurements as follows: working capital turnover, cash turnover, inventory turnover, and return on investment. This research shows that independent variable significanly are affecting independent variable. R-square 26,2 % shows that working capital turnover, cash turnover dan inventory turnover have significance contribution for return on investment.